Operationalizing the biocultural perspective part II: A review of biocultural action principles since The Declaration of Belém - Wall Jeffrey; Lukawiecki Jessica; Young Rachel; Powell Lara; McAlvay Alex; Moola Faisal (ElSevier, 2025)
In part 1 of our review of the biocultural conservation literature - conducted in 2019 - we utilized a rapid appraisal approach to determine that while the biocultural perspective was born within the action-oriented and Indigenous People and Local Community (IPLC)-Centered Declaration of Belém, the subsequent scientific discussion remained largely in a conceptual holding pattern. In Part 2, we reengage the literature later in time - mid-2021 - and with a more intensive qualitative analysis methodology to pursue the trends we observed and to more deeply perceive and comprehend the operating principles of the most impactful biocultural action research, which we define as research that fulfills the clear prescriptions of the Declaration of Belém. Toward these ends, we develop and utilize a systematic review methodology including thematic analysis, appreciative inquiry, and collaborative analysis. Our findings not only show an increasing concentration of action-orientation in the emerging literature, but identify and increase comprehension of the core operating principles for biocultural action. We determine that biocultural studies adhered to the following principles: 1) honor IPLC place attachment; 2) rigorously engage with IPLC's; 3) valorize cultural survival and continuity; 4) invert power dynamics; and 5) cultivate new insights. Our results represent a one-of-a-kind diagnostic on the fulfillment of the Declaration of Belém's prescriptions in conservation scholarship and practice, as well as a roadmap for practicing scholars and policy-makers intent on guaranteeing IPLC environmental leadership. These newly forged resources further point the way toward understanding and operationalizing the biocultural perspective as a strategic vision.